Determination of the Caving Zone and Fracture Zone Heights by Using the LK-Means Algorithm - Ze Zhou; Juncai Cao; Long Lai; Jinlian Zhou; Mengtang Xu (Advances in Civil Engineering)
The caving zone and fracture zone frequently appear after coal excavation. However, the caving zone and fracture zone can hardly be obtained with an empirical equation. Therefore, identifying a proper method to determine the caving zone and fracture zone is critically important to engineering practice. In this paper, Universal Distinct Element Code numerical simulations were conducted. Furthermore, the LK-means algorithm was used to determine the caving zone and fracture zone heights. To verify the validity of the proposed method, two engineering case studies were used. It could be found that the height calculated by the proposed method agrees well with that determined in engineering tests. Hence, the proposed method can be used in engineering practice.